PENGARUH PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN IPA TERPADU TERHADAP KEMAMPUAN KOGNITIF SISWA - RISDALINA, RISDALINA; YUSNAIDAR, YUSNAIDAR (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2023)
Cognitive abilities are very important for students to master because they relate to students' way of thinking at various cognitive levels. The facts that occur in the field are that teachers only train cognitive abilities up to understanding level (C2), students' cognitive ability scores are low, and students are rarely involved in practical activities. For this reason, it is necessary to address how to improve students' cognitive abilities. The scientific approach and integrated science learning are considered to be able to improve students' cognitive abilities. Integrated science learning is science learning that is holistic and meaningful for students so that it is easier to understand. Apart from that, a scientific approach can be presented using experimental methods. Therefore, this research aims to determine the effect of the scientific approach in integrated science learning on students' cognitive abilities. This research uses a weak experimental design method, the one group pretest-posttest design type. The research was conducted at one of the state junior high schools in Bandung City with 25 class VII H students as samples. The research instruments used were pretest and posttest cognitive ability questions. The pretest and posttest results of students' cognitive abilities were analyzed using the paired t-test, obtaining a significance value of 0.0005 on sig. (2-tailed), this shows that the scientific approach in integrated science learning with the webbed model has a significant effect on increasing students' cognitive abilities. ABSTRAKKemampuan kognitif sangat penting untuk dikuasai oleh siswa karena berkaitan dengan cara berfikir siswa dalam berbagai tingkatan kognitif. Fakta yang terjadi di lapangan, guru hanya melatihkan kemampuan kognitif sampai level memahami (C2), skor kemampuan kognitif siswa rendah, dan siswa jarang dilibatkan pada kegiatan praktikum. Untuk itu perlu diatasi bagaimana untuk meningkatkan kemampuan kognitif siswa. Pendekatan saintifik dan pembelajaran IPA terpadu dianggap dapat meningkatkan kemampuan kognitif siswa. Pembelajaran IPA terpadu merupakan pembelajaran IPA yang holistik dan bermakna bagi siswa sehingga lebih mudah untuk dipahami. Selain itu pendekatan saintifik bisa disajikan menggunakan metode eksperimen. Oleh karena itu, penelitian ini bertujuan untuk mengetahui pengaruh pendekatan saintifik dalam pembelajaran IPA terpadu terhadap kemampuan kognitif siswa. Penelitian ini menggunakan metode rancangan weak experimental tipe the one group pretest-posttest design. Penelitian dilakukan di salah satu SMP Negeri di Kota Bandung dengan 25 orang siswa kelas VII H sebagai sampel. Instrumen penelitian yang digunakan adalah soal pretest dan posttest kemampuan kognitif. Hasil pretest dan posttest kemampuan kognitif siswa dianalisis menggunakan uji paired t-test didapat nilai signifikansi 0,0005 pada sig. (2-tailed), hal ini menunjukkan bahwa pendekatan saintifik dalam pembelajaran IPA terpadu model webbed secara signifikan berpengaruh terhadap peningkatan kemampuan kognitif siswa.